Osteosynthesis of Unstable Fractures of Distal Radius with Volar Locking Plate - Pradhan, RL; Sharma, S; Pandey, BK; Manandhar, RR; Lakhey, S; Rijal, KP (Nepal Orthopaedic Association Journal, 2013)
Background: Various surgical treatment methods are available for unstable distal radius fractures. Clinical and radiological outcome with volar locking plate has been very satisfactory. The purpose of this prospective study is to evaluate the results of the treatment of unstable fractures with the volar locking plate with regard to loss of reduction, functional outcome and complications. Methods: Unstable distal radius fractures were enrolled for the study from May 2008 until July 2010. All patients were treated with 3.5 mm distal radius volar locking plate and assessed by clinical and radiological examination. The clinical scoring chart modified by Cooney was used to evaluate the functional outcome. Results: Eighteen male and 12 female patients with the average age of 42.53 (range 30- 64years) were followed up for a period of 9 to 34 months (average.23 months). There were fourteen A3 fractures, nine C1 fractures, six C2 fractures, and one C3 fracture, whereas one had a Gustilo grade I open wound on the volar aspect. Seven of the fractures had associate fracture of the ulnar styloid. The functional outcome was excellent in 23 (76%), good in 6 (20%), fair in 1 (4%) and none had poor outcome. There were very few complications in our series. Conclusion: Unstable fractures of distal radius treated by open reduction with volar locking plate provides adequate fixation with no collapse in reduction and also have satisfactory functional outcome with minimal complications. DOI: http://dx.doi.org/10.3126/noaj.v2i1.8137 Nepal Orthopaedic Association Journal Vol.2(1) 2011: 27-34